IMPLEMENTATION OF SERVICE DOMINANT LOGIC (SDL) THEORY AND THE CONCEPT OF CO-CREATION IN ECHOLEF'S SUSTAINABLE PRODUCT INNOVATION - Handoyo, Sus; Marsasi, Endy Gunanto (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
This study analyzes the transformation of business models in the creative industry through the application of Service-Dominant Logic (SDL) and value co-creation as strategic efforts to strengthen competitiveness and support sustainable product innovation. The research focuses on the development of Echolef, a new division established to build a collaborative ecosystem grounded in creativity, cultural values, and environmental sustainability. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation to explore the interactions among companies, customers, and creative partners. The findings reveal that value co-creation practices facilitated through open dialogue, information access, transparency, and shared risk management enhance customer participation and enrich the experiential meaning of products. The Business Model Canvas mapping highlights that Echolef’s competitive strength stems from integrating creative design, cultural storytelling, and innovation in eco-friendly materials. SDL further enables a strategic shift from product-centric to service-oriented value creation, emphasizing experiences, interactions, and resource integration among ecosystem actors. Overall, the study confirms that innovation and creativity are essential in developing adaptive and sustainable business models aligned with evolving market dynamics and consumer preferences. In conclusion, the combined SDL and value co-creation approaches effectively strengthen competitiveness by generating relevant, authentic, and future-oriented collaborative value.